Synthesis of Natural Base Hydrogels by Using g-Radiation Polymerization of Protein and Acrylic Monomers - Sadeghi, Mohammad; Shafeie, Fatemeh; Mohammadinasab, Esmat (Asian Journal of Chemistry, 2012)
Several hydrogels were prepared using radiolytic polymerization of aqueous solutions of 2-acrylamido-2-methylpropane sulfonic acid containing appropriate comonomer such as acrylic acid. The hydrogels have been prepared at an irradiation dose of 30 kGy. The hydrogels obtained were characterized using swelling technique, thermal and spectroscopic analysis.